The Effect of Early Active Mobilization on Union Rate after Ulnar Shortening Osteotomy - Blackburn, Julia; Saqib, Rukhtam; Rooker, Jemma; Baumann, Andreas; Amirfeyz, Rouin (Journal of Wrist Surgery, 2019)
Background Ulnocarpal impaction occurs when there is excessive loading between the ulnar carpus and the distal ulna. Ulnar shortening osteotomies (USOs) decompress the ulnocarpal joint. Many studies have evaluated USO but none have considered the effect of early active mobilization on union rate.Questions Does early active mobilization affect rate of union following USO? Does early active mobilization affect rate of complications following USO?Patients and Methods We performed a retrospective review of 15 consecutive patients that underwent 16 USOs between 2011 and 2015. There were seven males and eight females. Median age at time of shortening osteotomy was 47 years (range: 11–63 years). The median time of the procedure was 62 minutes (range: 45–105 minutes) and the median change in ulnar variance was 5.5 mm (range: 0–10.5 mm). Six patients were initially immobilized in incomplete plaster casts postoperatively, while the remainder had only wool and crepe dressings. Early active mobilization commenced after the first postoperative visit at 12 days.Results There was a 100% union rate in our series and 12 patients were pain-free at final follow-up. However, three of the patients with the longest times to union were smokers. Additionally, some patients may have achieved union between follow-up clinic visits.Conclusion Early active mobilization after USO does not affect union rate. Prospective, randomized studies are required to investigate the effect of early active mobilization in light of factors known to increase time to union, such as smoking.Level of Evidence This is a Level IV, case series.
Keywords: ulnar shortening osteotomy; nonunion; early active mobilization